FORMING THE QUALITIES OF RESPONSIBILITY AND INITIATIVE IN FUTURE TEACHERS - Urozboev N.U (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, the process of development of responsibility and initiative is characterized by the functioning of an integrative upbringing and educational system, which reflects the new meaningful reality of socio-pedagogical design